2016
DOI: 10.3892/mco.2016.960
|View full text |Cite
|
Sign up to set email alerts
|

Testicular germ cell tumor: Short and long-term side effects of treatment among survivors

Abstract: Abstract. Long-term prognosis of germ cell tumor (GCT) types is excellent, however, treatment is associated with non-negligible complication rates and a negative impact on quality of life. The present study described treatment results in terms of survival, both short and long-term toxicity, and paternity rates in a cohort of patients treated at Jules Bordet Institute, University ULB of Brussels (Brussels, Belgium). The present study analyzed the data of a cohort of patients with GCT types. Pre-operative patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Botchan et al reported the use of ART in 70/682 patients who had cryobanked semen prior to cancer treatment, achieving 36 to-term pregnancies ( 179 ). The previously cited study by Ping et al ( 166 ) analyzed the reproductive outcome of 117 TC patients post-treatment, finding that 19 (26%) of the 73 patients attempting fatherhood had been successful through ART with fresh semen (11 patients) or cryobanked semen (8 patients), similar to the results of a later study by Gil et al ( 180 ). Zakova et al ( 181 ) found a higher pregnancy rate, at 47% (16/34 patients), and better results were also reported by Molnar et al ( 182 ) (57%; 4/7 patients).…”
Section: Paternity and Testicular Cancersupporting
confidence: 59%
“…Botchan et al reported the use of ART in 70/682 patients who had cryobanked semen prior to cancer treatment, achieving 36 to-term pregnancies ( 179 ). The previously cited study by Ping et al ( 166 ) analyzed the reproductive outcome of 117 TC patients post-treatment, finding that 19 (26%) of the 73 patients attempting fatherhood had been successful through ART with fresh semen (11 patients) or cryobanked semen (8 patients), similar to the results of a later study by Gil et al ( 180 ). Zakova et al ( 181 ) found a higher pregnancy rate, at 47% (16/34 patients), and better results were also reported by Molnar et al ( 182 ) (57%; 4/7 patients).…”
Section: Paternity and Testicular Cancersupporting
confidence: 59%
“…For metastatic cases, the International Germ Cell Cancer Collaborative Group (IGCCCG) has identified three prognostic groups: good, intermediate, and poor risk. With optimal management the 5‐year survival rate approximates 91%, 79% and 48% in metastatic disease with good, intermediate and poor prognosis . Depending on the prognostic group three or four cycles of BEP represent the standard of care for relapsed or metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…In this contest, improving knowledge and social support to caregivers could help to ameliorate patients' global health. Confirming this, depression symptoms are less frequent in patients living in couples (21). Taking care of a patient with cancer is described as a full-time job (22) and caregivers themselves often are in great need of psychological support.…”
Section: Caregiver Burdenmentioning
confidence: 52%